2017
DOI: 10.1093/gji/ggx136
|View full text |Cite
|
Sign up to set email alerts
|

ITRF2014 plate motion model

Abstract: For various geodetic and geophysical applications, users need to have access to a plate motion model (PMM) that is consistent with the ITRF2014 frame. This paper describes the approach used for determining a PMM from the horizontal velocities of a subset of the ITRF2014 sites away from plate boundaries, Glacial Isostatic Adjustment regions and other deforming zones. In theory it would be necessary to include in the inversion model a translational motion vector (called in this paper origin rate bias, ORB) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
180
2
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(195 citation statements)
references
References 20 publications
7
180
2
6
Order By: Relevance
“…After merging (also adding v re f ), the data contains continental drift that could dominant the visualialization. Therefore, plate movement was compensated using the model in [29] to show movement relative to a specific plate (Eurasian). The removed motion is basically an overall offset of several mm/y, plus a light ramp due to the LoS projection of the horizontal motion.…”
Section: Resultsmentioning
confidence: 99%
“…After merging (also adding v re f ), the data contains continental drift that could dominant the visualialization. Therefore, plate movement was compensated using the model in [29] to show movement relative to a specific plate (Eurasian). The removed motion is basically an overall offset of several mm/y, plus a light ramp due to the LoS projection of the horizontal motion.…”
Section: Resultsmentioning
confidence: 99%
“…This consistency is expected given that the GIA model was constrained by a large subset of the GPS data presented here. The difference of 0.3 mm yr −1 could be related to the uncertainty in the connection between the IGS08 frame and the center of mass, which we have ignored, and which for ITRF2014 was most recently put at 0.30 ± 0.18 mm yr −1 in the z component (Altamimi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For the North American plate, early studies using space‐geodetic data confirmed plate rigidity within the uncertainty of the observations (Argus & Gordon, ; Dixon et al, ; Kogan et al, ). As the number of Global Positioning System (GPS) stations grew over time, their position time series lengthened, and their velocity uncertainties decreased, two types of studies have emerged: One uses the GPS velocities to estimate intraplate strain rates (Calais et al, , ; Gan & Prescott, ; Ward, ), while the other identifies and delineates a subpart of the plate that exhibits rigidity within the measurement precision (Altamimi et al, , ; Argus et al, ; Blewitt et al, ). The conclusion from both types of studies is that a large part of intraplate North America fails to behave as one rigid entity and that ongoing glacial isostatic adjustment (GIA) is likely the main cause.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the mechanisms controlling the plate kinematics in the region appear to be scaledependent (Manighetti et al 2001a): While large-and regional-scale (100-1000 km) deformation is well described by steady-state rotation of rigid lithospheric blocks (McKenzie et al 1970;Acton et al 1991;Chu & Gordon 1998;Eagles et al 2002;McClusky et al 2010;Saria et al 2013;Schettino et al 2016;Altamimi et al 2017;Doubre et al 2017), the crust beneath Afar is too dissected by faulting and magmatic intrusions for rigidity concepts to apply at smaller (∼10 km) spatial scales (Makris & Ginzburg 1987;Bastow & Keir 2011).…”
Section: Introductionmentioning
confidence: 99%